A game study on the impact of employees’ deviant innovation behaviors on firms’ organizational innovation performance - Zheng, Han; Lu, Jie; Chen, Yanxia; Gu, Yingying; Zheng, Zixin (Frontiers in Physics, 2024)
Organizational innovation performance is considered to be the key to maintaining competitiveness and achieving sustainable development in modern enterprises. Deviant innovation refers to that employees improve their working methods without the permission of the organization, break through the constraints of existing rules and achieve high performance.Additionally, Deviant innovation behavior can also stimulate the enthusiasm of other members of the organization. In order to study the evolutionary game rules of strategic interaction between enterprises and employees in the process of deviant innovation, this paper constructs a 2*2 asymmetric payoff matrix, and uses numerical simulation to show the influence of different values of decision parameters and changes of initial conditions on the evolutionary results. The research reveals that the interaction game between employees' deviant innovation behavior and enterprise enhancement of organizational innovation performance is a complex and significant topic. It is found that when enterprises actively improve organizational innovation performance and employees implement deviant innovation behavior, both sides engage in positive game interactions, maximizing enterprise benefits. However, when enterprises passively enhance organizational innovation performance but employees engage in deviant innovation behavior, it may lead to conflicts between the two parties. The research findings provide relevant strategies for employees to correctly implement deviant innovation behavior and for enterprises to enhance organizational innovation performance.